Recent progress in flexible Zn‐ion hybrid supercapacitors: Fundamentals, fabrication designs, and applications - Muhammad Sufyan Javed; Sumreen Asim; Tayyaba Najam; Muhammad Khalid; Iftikhar Hussain; Awais Ahmad; Mohammed A. Assiri; Weihua Han (Carbon Energy, 2023)
Abstract One of the most exciting new developments in energy storage technology is flexible Zn‐ion hybrid supercapacitors (f‐ZIHSCs), which combine the high energy of Zn‐ion batteries with high‐power supercapacitors to satisfy the needs of portable flexible electronics. However, the development of f‐ZHSCs is still in its infancy, and there are numerous barriers to overcome before they can be widely implemented for practical applications. This review gives an up‐to‐date description of recent achievements and underlying concepts in energy storage mechanisms of f‐ZIHSCs and emphasizes the critical role of cathode, anode, and electrolyte materials systems in speeding the prosperity of f‐ZIHSCs. The innovative nanostructured‐based cathode materials for f‐ZIHSCs include carbon (e.g., porous carbon, heteroatom‐doped carbon, biomass‐derived porous carbon, graphene, etc.), metal‐oxides, MXenes, and metal/covalent‐organic frameworks, and other materials (e.g., activated carbon, phosphorene, etc.) are mainly focused. Afterward, the latest developments in flexible anode and electrolyte frameworks and impacts of electrolyte compositions on the electrochemical properties of f‐ZIHSC are elaborated. Subsequently, the advancements based on fabrication designs, including quasi‐solid‐state, micro, fiber‐shaped, and all climate‐changed f‐ZIHSCs, are discussed in detail. Lastly, a summary of current challenges and recommendations for the future progress of advanced f‐ZIHSC are addressed. This review article is anticipated to further understand the viable strategies and achievable approaches for assembling high‐performance f‐ZIHSCs and boost the technical revolutions on cathode, anode, and electrolytes for f‐ZIHSC devices.